Family firms and family constitution - Fleischer, Holger; Prigge, Stefan (Law and management of family firms, 2023)
The ebook edition of this title is Open Access and freely available to read online. Family constitutions in family-owned firms are becoming increasingly popular around the world. While some, though not much, research examining this trend has come from a management research perspective, legal scholarship of family constitutions is even scarcer. The first volume of this new series brings together chapters from the 'Law and Management of Family Firms' conference which took place at the Max Planck Institute for Comparative and International Private Law, Hamburg, presenting legal, managerial, historical and comparative perspectives of family constitutions. Family Firms and Family Constitution delves deeply into topics as diverse as ownership, succession, governance, justice and more, all from a managerial and legal perspective from around the world. The pioneering Law and Management of Family Firms series publishes volumes following the annual Hamburg Conference: Law and Management of Family Firms, the international and interdisciplinary forum for family business research. The conference is organized by the Max Planck Institute and the Institute for Mittelstand and Family Firms (HSBA Hamburg School of Business Administration). It brings together two distinct and previously disconnected disciplines of law and management, benefiting scholars, lawyers, consultants, and family office practitioners.